2022
DOI: 10.1038/s41467-022-33299-5
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial diet modulates tamoxifen-induced death via host fatty acid metabolism

Abstract: Tamoxifen is a selective estrogen receptor (ER) modulator that is used to treat ER-positive breast cancer, but that at high doses kills both ER-positive and ER-negative breast cancer cells. We recapitulate this off-target effect in Caenorhabditis elegans, which does not have an ER ortholog. We find that different bacteria dramatically modulate tamoxifen toxicity in C. elegans, with a three-order of magnitude difference between animals fed Escherichia coli, Comamonas aquatica, and Bacillus subtilis. Remarkably,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…These findings suggest that innate adaptive mechanisms and host–diet interactions further alter the trajectory of stress responses. Moreover, that recent study also provided a scenario whereby, in response to an injury, some components, including oxidative status and cell death machinery, could themselves be entangled 29 . Additional recent findings show that ROS acting on dietary lipids compromises germ cell survival via ferroptosis and this can be alleviated by antioxidants 30 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggest that innate adaptive mechanisms and host–diet interactions further alter the trajectory of stress responses. Moreover, that recent study also provided a scenario whereby, in response to an injury, some components, including oxidative status and cell death machinery, could themselves be entangled 29 . Additional recent findings show that ROS acting on dietary lipids compromises germ cell survival via ferroptosis and this can be alleviated by antioxidants 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous work analysing cell death factors, including ced-3 caspase and ced-4 Apaf, enhanced survival under stressful conditions through an unknown mechanism 4 . More recent work using a tamoxifen-induced ROS model demonstrated that the extent of lipid oxidative stress is modulated by the interplay of dietary fatty acids, host fatty acid metabolism and cell death pathways 29 . These findings suggest that innate adaptive mechanisms and host–diet interactions further alter the trajectory of stress responses.…”
Section: Discussionmentioning
confidence: 99%
“…Our data not only confirm the connection between the methionine cycle, choline and lipid metabolism but also show that fatty acid levels affect cell fate specification during vulval development. The fatty acid metabolism affects C. elegans in many ways, by regulating survival, developmental time, reproduction, ferroptosis and modulating drug effects (Brock et al, 2007; Diot et al, 2022; Goudeau et al, 2011; Lemieux and Ashrafi, 2016; Perez and Watts, 2021; Perez et al, 2020). However, our data point to specific functions of the different fatty acids, as only oleic acid inhibited VPC differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…[13] In C. elegans, a poikilotherm, the most abundant types of fatty acids are PUFAs, primarily eicosapentaenoic acid (EPA; C20:5n3), followed by monounsaturated fatty acids (MUFAs) or monomethylbranched chain fatty acids (mmBCFAs) depending on the diet, and only a small fraction being SFAs. [13,38] At least two PAQR proteins contribute to membrane homeostasis in C. elegans: PAQR-1 and PAQR-2, with PAQR-2 playing a more important role and therefore better studied. PAQR-2 (encoded by the ORF Y32H12A.5) is 581 aa-long, with a large intracellular N-terminal domain of 313 aa, and a 52-aa extracellular C-terminal domain [37] (Figure 1A).…”
Section: Paqrs In the Nematode C Elegansmentioning
confidence: 99%